Dosimetric characteristics of an electron multileaf collimator for modulated electron radiation therapy - Eldib, Ahmed A. (J Appl Clin Med Phys, 2010)
Modulated electron radiation therapy (MERT) has been proven as an effective way to deliver conformal dose distributions to shallow tumors while sparing distal critical structures and surrounding normal tissues. It had been shown that a dedicated electron multileaf collimator (eMLC) is necessary to reach the full potential of MERT. In this study, a manually‐driven eMLC for MERT was investigated. Percentage depth dose (PDD) curves and profiles at different depths in a water tank were measured using ionization chamber and were also simulated using the Monte Carlo method. Comparisons have been performed between PDD curves and profiles collimated using the eMLC and conventional electron applicators with similar size of opening. Monte Carlo simulations were performed for all electron energies available (6, 9, 12, 15, 18 and 20 MeV) on a Varian 21EX accelerator. Monte Carlo simulation results were compared with measurements which showed good agreement [Formula: see text]. The simulated dose distributions resulting from multiple static electron fields collimated by the eMLC agreed well with measurements. Further studies were carried out to investigate the properties of abutting electron beams using the eMLC, as it is an essential issue that needs to be addressed for optimizing the MERT outcome. A series of empirical formulas for abutting beams of different energies have been developed for obtaining the optimum gap sizes, which can highly improve the target dose uniformity. PACS numbers: 87.53.Wz, 87.53.Hv